Heat stress, hydration and uric acid: a cross-sectional study in workers of three occupations in a hotspot of Mesoamerican nephropathy in Nicaragua. Issue 12 (8th December 2016) - Wesseling, Catharina; Aragón, Aurora; González, Marvin; Weiss, Ilana; Glaser, Jason; Rivard, Christopher J; Roncal-Jiménez, Carlos; Correa-Rotter, Ricardo; Johnson, Richard J
Abstract : Objectives: To study Mesoamerican nephropathy (MeN) and its risk factors in three hot occupations. Design: Cross-sectional. Setting: Chinandega and León municipalities, a MeN hotspot on the Nicaraguan Pacific coast, January–February 2013. Participants: 194 male workers aged 17–39 years: 86 sugarcane cutters, 56 construction workers, 52 small-scale farmers. Outcome measures: (1) Differences between the three occupational groups in prevalences/levels of socioeconomic, occupational, lifestyle and health risk factors for chronic kidney disease (CKD) and in biomarkers of kidney function and hydration; (2) differences in prevalences/levels of CKD risk factors between workers with reduced estimated glomerular filtration rate (eGFRCKD-EPI <80 mL/min/1.73 m 2 ) and workers with normal kidney function (eGFRCKD-EPI ≥80 mL/min/1.73 m 2 ). Results: Sugarcane cutters were more exposed to heat and consumed more fluid on workdays and had less obesity, lower blood sugar, lower blood pressure and a better lipid profile. Reduced eGFR occurred in 16%, 9% and 2% of sugarcane cutters, construction workers and farmers, respectively (trend cane > construction > farming, p=0.003). Significant trends (cane > construction > farming) were also observed for high serum urea nitrogen (blood urea nitrogen (BUN) >20 mg/dL), high serum creatinine (SCr >1.2 mg/dL), low urinary pH (≤5.5) and high BUN/SCr ratio (>20) but not for high urinary specific gravity (≥1.030). Sugarcane cutters also more often had proteinuria and blood and leucocytes in the urine. Workers with eGFR <80 mL/min/1.73 m 2 reported a higher intake of water and lower intake of sugary beverages. Serum uric acid levels related strongly and inversely to eGFR levels (adj β −10.4 mL/min/1.73 m 2, 95% CI −12.2 to −8.5, p<0.001). No associations were observed for other metabolic risk factors, pesticides, non-steroidal anti-inflammatory drugs or alcohol. Among cane cutters, consumption of electrolyte hydration solution appeared preventive (adj β 8.1 mL/min/1.73 m 2, p=0.09). Conclusions: Heat stress, dehydration and kidney dysfunction were most common among sugarcane cutters. Kidney dysfunction also occurred to a lesser extent among construction workers, but hardly at all among small-scale farmers. High serum uric acid was associated with reduced kidney function.